2018
DOI: 10.1021/acs.jpcc.8b03972
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Speciation of Naphthalene Vapor Deposited on Ice Surfaces at 253 or 77 K: Formation of Submicrometer-Sized Crystals or an Amorphous Layer

Abstract: Naphthalene was deposited from the vapor phase on ice surfaces at 77 or 253 K to yield strongly distinct behavior, forming either an amorphous glass layer or submicrometer-sized crystals, respectively. The results stand upon optical emission spectroscopy combined with differential scanning calorimetry and X-ray analysis. The amorphous layer of naphthalene on the ice behaves in the same manner as on an inert metallic support: it starts to relax at 105 K and crystallizes at 185 K. The formed microcrystals exhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 105 publications
3
15
0
Order By: Relevance
“…Subsequent breaking of the ice into small pieces was proposed to bring the impurities to the ice surface (Kahan et al, 2010); this assumption was recently questioned (Hullar et al, 2018). Other studies suggested that freezing an aqueous solution places the impurities prevalently inside the ice interior, whereas deposition of the organics from the vapor phase accommodates them on the ice surface (Ondrušková et al, 2018;Vetráková et al, 2017;Krausko et al, 2015a, b;Kania et al, 2014;Heger et al, 2011;Hullar et al, 2018;Bartels-Rausch et al, 2013). Conversely, nebulizing the solution into liquid nitrogen was assumed to produce ice spheres with the organic impurities on their surfaces (Kurkova et al, 2011).…”
Section: L' Vetráková Et Al: a Study Of The Freezing Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent breaking of the ice into small pieces was proposed to bring the impurities to the ice surface (Kahan et al, 2010); this assumption was recently questioned (Hullar et al, 2018). Other studies suggested that freezing an aqueous solution places the impurities prevalently inside the ice interior, whereas deposition of the organics from the vapor phase accommodates them on the ice surface (Ondrušková et al, 2018;Vetráková et al, 2017;Krausko et al, 2015a, b;Kania et al, 2014;Heger et al, 2011;Hullar et al, 2018;Bartels-Rausch et al, 2013). Conversely, nebulizing the solution into liquid nitrogen was assumed to produce ice spheres with the organic impurities on their surfaces (Kurkova et al, 2011).…”
Section: L' Vetráková Et Al: a Study Of The Freezing Methodsmentioning
confidence: 99%
“…However, the information combining the reactivity of compounds with their locations is essentially missing. Excepting low concentrations of HF, NH + 4 , HCl, HNO 3 , and formaldehyde (Perrier et al, 2002;Domine, 1998, 1997), impurities are usually not incorporated into the ice lattice (Krausková et al, 2016;Hobbs, 2010;Wilson and Haymet, 2008). As ice is highly intolerant to impurities, these are segregated to an unfrozen freeze-concentrated solution (FCS) during the growth of ice crystals.…”
Section: Introductionmentioning
confidence: 99%
“…The FCS was found to behave distinctly from the impurities deposited from the gaseous phase. 44,45 The impurities segregated from the ice either create pools or fill the pores between two ice crystals on the surfaces; where, however, three ice grains meet in the ice bulk volume, triple junction tubes (also termed veins) may emerge. 36,46 The diameters of the observed venous filaments formed by deep freezing of NaCl FCSs in between partly sublimed ice I h crystals varied from 0.2 to 2.5 µm.…”
Section: Introductionmentioning
confidence: 99%
“…Clustering of PAHs on atmospherically-relevant surfaces such as mineral dust and silica has been inferred based on emission spectra, 29,[40][41][42][43][44] and several studies have reported different photochemical or heterogeneous reaction kinetics of aromatic species at a range of environmental surfaces compared to in aqueous solution. 15,40,41,[43][44][45] Theoretical and experimental studies have also demonstrated clustering of species including oleic acid, 46 naphthalene, 15,47 and glyoxal 48 on atmospherically-relevant surfaces including polystyrene and ice. The insights gained from this work may therefore help explain heterogeneous reaction kinetics of other atmospherically relevant organic species at a range of surfaces, and the techniques applied in this work are widely applicable to atmospheric surfaces other than ice, and to surfaces relevant to research areas such as biology and materials science.…”
Section: Discussionmentioning
confidence: 99%
“…Emission and excitation spectra of some aromatic molecules at air-ice interfaces acquired by surface-selective LIF show red shifts compared to spectra in dilute aqueous solution, indicative of self-association. [13][14][15][16] We have recently reported that anthracene molecules in liquid aqueous solution photodegrade much more rapidly at concentrations well above the saturation limit where spectroscopic evidence of self-association is observed than in dilute solutions, and that the photodegradation kinetics shift from 1 st to 2 nd order at these high concentrations. 17 We have hypothesized that aromatic species form clusters at ice surfaces, and that self-associated anthracene molecules in these clusters react via different mechanisms than monomeric anthracene in liquid water or at air-water interfaces.…”
Section: Introductionmentioning
confidence: 99%